RUWATAN : TINJAUAN ALKITABIAH - A. Hari Kustono (Litbang STFT Widya Sasana Malang, 2006)
Ruwatan is part of Javanese tradition about the rite of salvation. It is a ritual traditional event by performing wayang puppets with the story of Murwakala, with purpose to live safely and happily, to avoid of becoming victims of Batara Kala, a bad son of god Guru. Those who are regarded as the victims of Batara Kala are called sukerta. This Ruwatan performance is considered as very sacred, it must be prepared carefully. In these recent days, actually the Ruwatan ritual, if it is performed for the public, has been simplified. Only the really crucial stages are held, such as siraman (bathing), having the hair cut, and the puppet show. Some of the Christian people still keep this tradition. It is true that ruwatan contains several moral and religious values. However, the adoption of this traditional rite to be a Christian ceremony needs several modifications and changes. This article offers some suggestions to reflect the ruwatan in the light of biblical perspectives.